Recent advances in the development of ammonia borane for both energetic and energy storage materials - Rui Pu; Yunlong Zhang; Shaoli Chen; Qilong Yan (Propulsion and Power Research)
Ammonia borane (NH3BH3) has garnered significant attention as a high-potential hydrogen storage material owing to its exceptional hydrogen content of 19.6 wt%. This remarkable capacity positions it as a promising candidate for energetic applications, including next-generation solid propellants. However, its practical utility in such systems is limited by its inherently low decomposition temperature, which compromises stability under operational conditions. Over the past two decades, extensive research has focused on enhancing ammonia borane's properties through structural and chemical modifications, resulting in notable progress. Despite these advancements, a systematic review synthesizing modification strategy and their implications for energetic material applications remains absent. To address this gap, this review systematically compiles recent advances in ammonia borane modification and critically evaluates its evolving role in energetic material development, offering insights into future research directions.